ANALISIS RISIKO PAJANAN GAS AMMONIA (NH3) PADA PEKERJA DI BAGIAN PABRIK AMMONIA I PT PETROKIMIA GRESIK - Dinda Dwi Firmansyah; Khambali .; Koerniasari . (Poltekkes Kemenkes Surabaya, 2020)
ABSTRACT PT Petrokimia Gresik is the Complete Fertilizer Manufacturer in Indonesia which produces various kinds of fertilizers and chemicals for agro-industrial solutions. Ammonia (NH3) is one of the results of chemical production at PT Petrokimia Gresik which poses a risk to the health of ammonia factory workers at PT Petrokimia Gresik. The purpose of this study is to analyze the risk of exposure to ammonia (NH3) gas in ammonia I factory workers of PT Petrokimia Gresik.This study is a descriptive survey using Environmental Health Risk Analysis approach. The data analysis method used was risk analysis to determine the risk characterization of PT Petrokimia Gresik ammonia (NH3) I workers. The level of risk is said to be safe if RQ ≤ 1, and the level of risk is said to be unsafe if RQ 1.The results showed that the average concentration of ammonia (NH3) gas was 6.6 mg / m3, the highest concentration was 9.2 mg / m3, the lowest concentration was 4.3 mg / m3. The physical air environment obtained at an average air temperature of 36oC, the average air humidity was 43%, the average wind speed was 0.85 m / s and the wind direction when the measurements blew from the West and East. Agents at risk of causing health problems to workers at ammonia I factory of PT Petrokimia Gresik were ammonia (NH3) gas in the work environment air sourced from the ammonia (NH3) gas production process, and 57% of the ammonia I factory workers of PT Petrokimia Gresik had a history of respiratory disorder. The response dose of ammonia (NH3) gas was 5x10-1 mg / m3. All ammonia I factory workers at PT Petrokimia Gresik obtained a minimum concentration, average concentration and maximum concentration of RQ 1.From the results of the study it can be concluded that the level of risk of exposure to ammonia (NH3) gas in ammonia I factory workers of PT Petrokimia Gresik is safe and not at risk of developing respiratory tract disorders, because the concentration is minimal, average concentration and maximum concentration does not exceed risk (RQ). It is recommended that the ammonia I plant manager of PT Petrokimia Gresik keep monitoring and evaluating the air pollution control and prevention system regularly. Key words: Risk Analysis, Ammonia Gas (NH3), Workers